Contributions of Kaufmann’s comprehensive interview for the Interpretive Policy Analysis - Nathália Gonçalves Ferreira; Gustavo Costa de Souza (Revista Aval, 2023)
The work presents the Comprehensive Interview (Kaufmann, 2013) as a relevant method for the Interpretive Analysis Of Public Policy. In contrast to the first contributions of the rationalis era, critical and argumentative approaches took shape from 1990 onwards. Since then, traditional analysis models have been questioned by post-positivist propositions. One of these propositions is the argumentative turn (Fischer, 1993) that seeks to go beyond utilitarian concepts, including debate as an important tool for social inclusion. Thus, the focus becomes argumentation, discursiveness and social participation. Another proposition that comes under this influence, on a national level, is the Mirada ao Revés (Boullosa, 2013). From this thoretical repertoire, we place the Comprehensive Interview as a method that allows the approach of subjects in depth, therefore, promising for the analysis of public policies through the interpretive approach, based on its democratizing potential.